Climate policy priorities for the next European Commission - Clemens Fuest; Andrei Marcu; Michael Mehling (CESifo GmbH, 2024)
From the earliest announcement of the European Green Deal, the current EU political cycle has been defined by an unprecedented acceleration in the scale and pace of climate policy. Under difficult conditions that sometimes tested the ability to engage stakeholders, including various external shocks, the EU has put forward and largely passed an unprecedented legislative agenda, which was meant to have, and is having, deep impacts on the EU economy and society at large. Much has changed in the world since the European Green Deal and the 'Fit for 55' packages were conceived, including a dramatic increase in industrial policy actions by Europe's trade partners, a deteriorating geopolitical landscape, and an energy crisis that has been aggravated by these factors, all of which has led to persistent fiscal and economic pressures. Given this reality, both the climate policy objectives and instruments pursued over the course of the last five years may need to be scrutinized in the coming political cycle, to ensure that they respond to evolving circumstances, concerns, and above all the reaction of European society to the political and economic consequences. Based on interviews and feedback from the members of a high-level Advisory Group as well as consultations with approximately 200 stakeholders from the public and private sectors, civil society, and research and academia convened in Berlin, Paris, and Warsaw, this report identifies climate policy priorities and formulates recommendations for the incoming European institutions. It groups these along several dimensions: overarching issues; international context and cooperation; interlinkages with other policy areas; policies and instruments; industrial competitiveness; and public support for the transition. On these issues, the report identifies challenges and relevant considerations, including macroeconomic impacts, that will need to be included in the evaluation of current policies and the development of new ones in order to meet the objectives on the EU Climate Law while securing an economically competitive and prosperous EU.
Keywords: 330; EU-Klimapolitik; Klimawandel; Dekarbonisierung; Wirkungsanalyse; EU-Staaten